2019
DOI: 10.1038/s41408-019-0249-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal embryonic leucine zipper kinase is a novel target for diffuse large B cell lymphoma and mantle cell lymphoma

Abstract: Diffuse large B cell lymphoma (DLBCL) and mantle cell lymphoma (MCL) are among the most aggressive B cell non-Hodgkin lymphomas. Maternal embryonic leucine zipper kinase (MELK) plays a role in cancer cell cycle progression and is associated with poor prognosis in several cancer cell types. In this study, the role of MELK in DLBCL and MCL and the therapeutic potential of MELK targeting is evaluated. MELK is highly expressed in DLBCL and MCL patient samples, correlating with a worse clinical outcome in DLBCL. Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Recently OTS167 has been shown to inhibit the MELK-dependent phosphorylation of eIF4B in human breast cancer cell lines, which resulted in downregulation of anti-apoptotic factor myeloid cell leukemia 1 (MCL-1) expression 30 . In human multiple myeloma (MM), diffuse large B cell lymphoma (DLBCL) and mantle cell lymphoma (MCL) cell lines, MCL-1 expression was also inhibited by OTS167, although by an unknown mechanism 40 , 41 . Here we show OTS167 inhibits phosphorylation of eIF4B in human FLT3 mutant cell lines, and in these cell lines loss of eIF4B expression results in the loss of FLT3-ITD expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently OTS167 has been shown to inhibit the MELK-dependent phosphorylation of eIF4B in human breast cancer cell lines, which resulted in downregulation of anti-apoptotic factor myeloid cell leukemia 1 (MCL-1) expression 30 . In human multiple myeloma (MM), diffuse large B cell lymphoma (DLBCL) and mantle cell lymphoma (MCL) cell lines, MCL-1 expression was also inhibited by OTS167, although by an unknown mechanism 40 , 41 . Here we show OTS167 inhibits phosphorylation of eIF4B in human FLT3 mutant cell lines, and in these cell lines loss of eIF4B expression results in the loss of FLT3-ITD expression.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in vivo inhibition of MELK activity through the inhibitor OTSSP167 in breast cancer xenograft models revealed that inhibition of MELK activity reduced the growth of basal-like cell breast cancer xenografts, but not of luminal cell breast cancer xenografts ( Wang et al 2014 ). Similarly, OTSSP167 significantly improved the survival of mice in which A20 lymphoma cells were transplanted, which suggests that blocking MELK activity in vivo can also inhibit lymphoma progression ( Maes et al 2019 ). Germline inactivation of MELK in mice does not yield an obvious phenotype during embryo development or in adult mice, indicating that MELK is dispensable for normal development ( Wang et al 2014 ).…”
Section: Introductionmentioning
confidence: 96%
“…Conversely, in vivo inhibition of MELK activity through the inhibitor OTSSP167 in breast cancer xenograft models revealed that inhibition of MELK activity reduced the growth of basal-like cell breast cancer xenografts, but not of luminal cell breast cancer xenografts [11,13]. Similarly, OTSSP167 significantly improved the survival of mice in which A20 lymphoma cells were transplanted, which suggests that blocking MELK activity in vivo can also inhibit lymphoma progression [14]. Germline inactivation of MELK in mice does not yield an obvious phenotype during embryo development or in adult mice, indicating that MELK is dispensable for normal development [5].…”
Section: Introductionmentioning
confidence: 99%